NEUROLOGICAL COMPLICATIONS OF AIDS - Kadirov J.F.; Gaybullaev Sh.O.; Shodmanov F.J.; Fayzullaev S.A. (Journal of new century innovations, 2022)
Summary. In the lecture, data were given about neurological complications In the syndrome of full immunodeficiency (AIDS), which occur In 50-60% of patients. The most widespread are encephalitis, meningitis, meningoencephalitis, polyneuropathy, myelopathy, myopathy. Ethiopathogenetic mechanisms of lhese complications, clinic, treatment, prognosis are being developed.